(untitled) (Medico Legal Update, 2021)
Background: Dental and oral health problems in the community can arise due to behavioral factors or attitudes ignoring oral and dental hygiene. The level of education and the factors that affect children’s own dental health have been presented in various studies. Objective: To analyze the relationship between socio-economic aspects and the level of education of people aged 18-25 years towards the habit of brushing teeth in the city of Surabaya. Method: This type of research is an observational analytic study with a design using a cross sectional study approach. In this study, related data were collected regarding the relationship between education and socioeconomic levels of the age range of 18-25 years on the habit of brushing properly taken at the same time. Results: There was no significant relationship between education and socio-economic level with the habit of brushing teeth. Conclusion: It was concluded that there was no significant relationship between education level with the habit of brushing teeth and the relationship of socioeconomic level with the habit of brushing teeth.